PENGARUH ERP, ICT DAN AUDIT INTERNAL TERHADAP KINERJA PERUSAHAAN DIMODERASI OLEH CAAT - Beth, Eliza; Agoes, Sukrisno (Jurnal Kontemporer Akuntansi, 2025)
The aim of this research is to study how ERP planning, ICT, and internal audit affect company performance. This research is moderated by audit tools and CAAT. The focus of this research is non-cyclical consumer companies listed on the Indonesia Stock Exchange (BEI) from 2016 to 2020. Quantitative methods were used in the research, which included surveys and documentation analysis for data collection. The research sample was taken using a purposive sampling method, and the data was analyzed using multiple regression techniques with the help of statistical software. This research found that ERP, ICT, and Internal Audit significantly improved company performance. In addition, this research also found that CAAT significantly improved ERP performance and company performance, but did not improve ICT and Internal Audit performance. By implementing ERP, using ICT, and improving internal audit practices, companies in the non-cyclical consumer subsector can improve their performance. A better understanding of CAAT's function in managing the relationship between corporate performance and ERP can also help management make better decisions.